Kompleksitas Reposisi dalam Linguistik Arab - Achmad Khusnul Khitam (Alfaz (Arabic Literatures for Academic Zealots), 2020)
This article aims to discuss the complexity occurs within the case of reposition. Conceptually, the case of reposition is similar to the notion of at-taqdīm wa at-ta’khīr in Arabic linguistic tradition. Previous studies concerning this case have been conducted, primarily to elaborate structural aspect of the case. This article aims to analyze three aspects of language, namely style (deviation), structure (relation), and meaning (implication). The result of this research shows that at least three linguistic aspects (style, structure, meaning) occur within the case of reposition at the same time. Those three aspects work simultaneously (mutazāmin wa mutaẓāfir) in each linguistic unit within the case. The reposition of a certain linguistic unit represents the deviation of the case, the connection attached between this unit to other existing units represents the relation of the case, whereas both deviation and relation can give direct implication to produce a certain meaning.